IDENTIFIKASI TANAMAN OBAT TRADISIONAL YANG DIPERGUNAKAN SUKU ANAK DALAM DESA DWI KARYA BAKTI, KABUPATEN BUNGO, PROVINSI JAMBI - Noerjoedianto, Dwi; Kalsum, Ummi; Halim, Rd.; Ridwan, M.; Dhermawan Sitanggang, Hendra; Suryani Nasution, Helmi; Listiawaty, Renny; Syafrila Wil Yantoni, Lara (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
One of the local wisdoms in Jambi Province is the Anak Dalam Tribe (SAD), which is known for its expertise in making traditional medicinal concoctions. This study aim was to identify traditional medicinal plants used by SAD in Dwi Karya Bakti Village, Bungo Regency, Jambi Province. Data collection from September to November 2023 using in-depth interviews, observation and documentation of medicinal plants, how to mix them and the types of diseases treated. Representative sampling of medicinal plants from the informants' routine locations for collecting medicinal plants. The results of this research grouped medicinal herbs into 5 groups of medicinal plants commonly used by the SAD community in Dwi Karya Bakti Village, namely groups for cough and sore throat medicines, diarrhea medicines, diseases in mothers and children, external medicines (boils, canker sores). and aches) as well as fever medication. The parts of the plant that most used were the leaves (38%), the least used were the flowers (5%) and roots (5%). The processing that most often done was used directly (73.50%) without boiling or burning, and the least processing method was boiling (10.5%). The most common ways of use were drinking (31.5%) and applying topically (31.5%), while the least ways by dropping it, making it into a necklace, tying it or bathing it at 5% each.